Anxious and non-anxious forms of major depression: familial, personality and symptom characteristics. Issue 6 (1st August 2013) - Goldberg, D. P.; Wittchen, H.-U.; Zimmermann, P.; Pfister, H.; Beesdo-Baum, K.
Abstract : Background: Earlier clinical studies have suggested consistent differences between anxious and non-anxious depression. The aim of this study was to compare parental pathology, personality and symptom characteristics in three groups of probands from the general population: depression with and without generalized anxiety disorder (GAD) and with other anxiety disorders. Because patients without GAD may have experienced anxious symptoms for up to 5 months, we also considered GAD with a duration of only 1 month to produce a group of depressions largely unaffected by anxiety. Method: Depressive and anxiety disorders were assessed in a 10-year prospective longitudinal community and family study using the DSM-IV/M-CIDI. Regression analyses were used to reveal associations between these variables and with personality using two durations of GAD: 6 months (GAD-6) and 1 month (GAD-1). Results: Non-anxious depressives had fewer and less severe depressive symptoms, and higher odds for parents with depression alone, whereas those with anxious depression were associated with higher harm avoidance and had parents with a wider range of disorders, including mania. Conclusions: Anxious depression is a more severe form of depression than the non-anxious form; this is true even when the symptoms required for an anxiety diagnosis are ignored. Patients with non-anxious depression are different from those with anxious depression in terms of illness severity, family pathology and personality. The association between major depression and bipolar disorder is seen only in anxious forms of depression. Improved knowledge on different forms of depression may provide clues to their differential aetiology, and guide research into the types of treatment that are best suited to each form.